Perceptions of dental students on their learning environment at the Faculty of Odonto-Stomatology, University of Health Sciences, Phnom Penh, Cambodia - Heng, Sopanha
The purpose of the study is to investigate dental students' perceptions of the learning environments at the Faculty of Odonto-Stomatology, University of Health Science, Kingdom of Cambodia. The characteristics of effective teachers have been shown to affect students learning. This will help the school of dentistry administrators get important new ideas for improvement of the teaching and learning setting. Competencies concerned with three domains are to develop rationale and scientific temperament, foresee advancements in all spheres of life and its impact on the society and help students in conserving and transmitting values nurtured by the society. The specific objectives of this study are to (1) to identify the perceptions of dental students on their learning environment, (2) to determine if the perceptions of dental students on learning environment vary according to students' gender and years of study. This study is a cross-sectional survey conducted among the 4th, 5th, 6th and 7th year dental students. Final student population consisted of 312 (male = 221 and female = 91). Data were analyzed using frequency distribution of genders, ages, mean ages, level of students' scores, using descriptive, crosstab statistics, the measures of central tendency especially the means and standard deviations. The survey used the translated questionnaire of the Dundee Ready Education Environment Measure (DREEM). Permission was given by Professor Susanne Roff (s.l.roff@dundee.ac.uk). Results show that students' perceptions on their learning environment vary across sites. The study finding also indicated that students' perception of effectiveness of learning affected how students perceived their learning environment experiences. Although these findings need to be confirmed, they provide grounds for looking at learning environment in a new light. Opportunities to implement learning environment that are most effective should be seized at every possible juncture. These actions will maximize opportunities for dental students to learn, and succeed in becoming a dental professional.